1999
DOI: 10.1046/j.1365-3083.1999.00535.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Subpopulations of T‐Cell Receptor Intermediate (TCRint) T Cells

Abstract: CD1-autoreactive T cells of two types have been demonstrated among T cells expressing the T-cell receptor (TCR) alphabeta at intermediate levels (TCRint cells). One type constitutes a major fraction of the natural killer (NK)1.1+ TCRint population in C57BL/6 (B6) mice and carries a restricted TCR composed of an alpha-chain with an invariant Valpha14-J281 rearrangement, and a beta-chain using Vbeta8. 2, 7 or 2. The second type utilises a variety of TCR and was derived from CD4+ cells in mice lacking MHC class I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 46 publications
0
10
1
Order By: Relevance
“…Peripheral 24␣ ϩ ␤ ϩ T cells shared characteristic features with NKT cells, including a phenotype of previous activation (CD44 high , CD62L low ), expression of CD122/IL-2R␤, intermediate levels of the TCR, and synthesis of high amounts of cytokines, IL-4 and IFN-␥, upon activation (12,18,35). The appearance of 24␣ ϩ ␤ ϩ T cells of the typical NKT phenotype required the presence of CD1d and the expression of both chains of the CD1d-reactive TCR.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Peripheral 24␣ ϩ ␤ ϩ T cells shared characteristic features with NKT cells, including a phenotype of previous activation (CD44 high , CD62L low ), expression of CD122/IL-2R␤, intermediate levels of the TCR, and synthesis of high amounts of cytokines, IL-4 and IFN-␥, upon activation (12,18,35). The appearance of 24␣ ϩ ␤ ϩ T cells of the typical NKT phenotype required the presence of CD1d and the expression of both chains of the CD1d-reactive TCR.…”
Section: Discussionmentioning
confidence: 99%
“…NKT cells have been shown to display a particular profile of cytokines when stimulated in vitro (12,18,35) and further to rapidly secrete high amounts of cytokines upon in vivo induction (19). To analyze the potential of transgenic T cells to produce cytokines, lymph node or spleen cells were polyclonally stimulated in vitro.…”
Section: Functional Characteristics Of Transgenic T Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, CD44 high cells expressed lower levels of the ␣␤TCR than the CD44 low cells. The lower expression of the ␣␤ TCR is characteristic of NKT cells (22) as well as the self-specific CD8 ϩ T cells that can develop via an extrathymic pathway (11). However, unlike NKT cells, immediately ex vivo CD8 ϩ CD44 high cells do not express NK1.1 or significant levels of other NK receptors such as CD94, 2B4 or NKG2D (Fig.…”
Section: Cd8mentioning
confidence: 97%
“…Analyses of the CD1d-restricted CD4 ϩ compartment in mice lacking MHC class II molecules (I-A␤ Ϫ/Ϫ C57BL/6 mice) have shown that it can be subdivided into NK1.1 ϩ and NK1.1 Ϫ cell populations, whose TCR repertoire was found to be skewed toward V␤8 segments (4, 26 -28). Moreover, Sköld et al (28) demonstrated that some of these cells express the V␣14-J␣281 rearrangement typical of NK1.1 ϩ T cells. To date, ␣-GalCer reactivity during primary cultures has been investigated exclusively in the NK1.1 ϩ T cell subset (24).…”
mentioning
confidence: 99%